Identification of Circulating miRNAs in a Mouse Model of Nerve Allograft Transplantation under FK506 Immunosuppression by Illumina Small RNA Deep Sequencing. (8th September 2015) - Wu, Shao-Chun; Rau, Cheng-Shyuan; Yang, Johnson Chia-Shen; Lu, Tsu-Hsiang; Wu, Yi-Chan; Chen, Yi-Chun; Tzeng, Siou-Ling; Wu, Chia-Jung; Lin, Chia-Wei; Hsieh, Ching-Hua
Abstract : Background . This study aimed to establish the expression profile of circulating microRNAs (miRNAs) during nerve allotransplantation in the presence and absence of FK506 immunosuppression. Methods . A 1 cm BALB/c donor sciatic nerve graft was transplanted into the sciatic nerve gaps created in recipient C57BL/6 mice with or without daily FK506 immunosuppression [1 mg/(kg·d)]. At 3, 7, and 14 d after nerve allotransplantation, serum samples were collected for miRNA expression analysis by Illumina small RNA deep sequencing. Results . Sequence analysis showed that the dominant size of circulating small RNAs after nerve allotransplantation was 22 nucleotides, followed by 23-nucleotide sequences. Nine upregulated circulating miRNAs (let-7e-5p, miR-101a-3p, miR-151-5p, miR-181a-5p, miR-204-5p, miR-340-5p, miR-381-3p, miR-411-5p, miR-9-5p, and miR-219-2-3p) were identified at 3 d, but none was identified at 7 or 14 d. Among them, miR-9-5p had the highest fold-change of >50-fold, followed by miR-340-5p with 38.8-fold. The presence of these nine miRNAs was not significant at 7 and 14 d after nerve allotransplantation with or without immunosuppression, showing that these miRNAs are not ideal biomarkers for monitoring rejection of deep-buried nerve allografts, a response usually observed later. Conclusions . We identified nine upregulated circulating miRNAs, which may have a biological function, particularly during the early stages after nerve allotransplantation under FK506 immunosuppression.